Rushing into American dream? House prices, timing of homeownership, and adjustment of consumer credit - Sumit Agarwal; Luojia Hu; Xing Huang (Federal Reserve Bank of Chicago, 2013)
In this paper we use a large panel of individuals from Consumer Credit Panel dataset to study the timing of homeownership as a function of credit constraints and expectations of future house price. Our panel data allows us to track individuals over time and we model the transition probability of their first home purchase. We find that in MSAs with highest quartile house price growth, the median individual become homeowners earlier by 5 years in their lifecycle compared to MSAs with lowest quartile house price growth. The result suggests that the effect of expectation dominates the effect of credit constraints and high price growth leads individuals to purchase home earlier. We further study other credit/loan behaviors around first-home purchases for young and old buyers. We find that younger buyers make more adjustments in their finances after the purchase - taking out more debt/credit, and yet they do not appear to experience larger increase in delinquency than older buyers.
Keywords: R21; D12; D91; D14; 330; Housing; Homeownership; Consumer Finance; Credit Constraints; Life Cycle